Consumer Behavior Analysis: Factors that Influence Online Buying Decisions - Sharma, Luxmi (Devkota Journal of Interdisciplinary Studies, 2023)
Online shopping’s rise in popularity in Nepal is due to its multiple advantages like 24/7 availability, ease of use, and extensive product options. However, this comes with certain risks including financial loss and security concerns. This study, drawing from contemporary literature and data from 385 respondents from varied backgrounds, aims to identify these risks and psychological factors that affect buying decisions. Key findings indicate a notable influence of financial risks, while delivery and trust issues have a moderate impact, suggesting that e-retailers should focus on addressing these aspects to bolster online sales.